2022
DOI: 10.1186/s12245-022-00444-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of out-of-hospital cardiac arrest patients before and during the COVID-19 pandemic in Thailand

Abstract: Background Out-of-hospital cardiac arrest (OHCA) remains one of the leading causes of death worldwide, and bystander CPR with public-access defibrillation improves OHCA survival outcomes. The COVID-19 pandemic has posed many challenges for emergency medical services (EMS), including the suggestion of compression-only resuscitation and recommendations for complete personal protective equipment, which have created operational difficulties and prolonged response time. However, the risk factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…A total of ten studies were included in the analysis of CPR using mechanical CPR devices, with six studies showing significant results. Among them, a significant increase in CPR with mechanical CPR devices during the COVID-19 pandemic was reported in three studies ( 34 , 57 , 71 ), and a significant decrease was reported in the other studies ( 13 , 78 , 98 ). Talikowska et al noted that the increase in the number of patients who stopped CPR in the field could be explained by the desire to follow local protocols, and a decrease in the number of people who required CPR using mechanical CPR devices ( 78 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A total of ten studies were included in the analysis of CPR using mechanical CPR devices, with six studies showing significant results. Among them, a significant increase in CPR with mechanical CPR devices during the COVID-19 pandemic was reported in three studies ( 34 , 57 , 71 ), and a significant decrease was reported in the other studies ( 13 , 78 , 98 ). Talikowska et al noted that the increase in the number of patients who stopped CPR in the field could be explained by the desire to follow local protocols, and a decrease in the number of people who required CPR using mechanical CPR devices ( 78 ).…”
Section: Discussionmentioning
confidence: 97%
“…The frequency of percutaneous coronary intervention reported by Ahn et al, Riyapan et al, and Phattharapornjaroen et al and the frequency of emergency coronary angiography reported by Sultanian et al did not show significant differences before and during the COVID-19 pandemic. Therefore, it can be assumed that the impact of the COVID-19 pandemic on the hospital-stage treatments of OHCA patients may be low; however, interpretation is limited because meta-analyses were not performed due to the small number of studies ( 34 , 71 , 73 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…By the end of this study’s period, the STA rate had slightly increased to 6.7% in the first 5 months of 2023 but remained approximately 65% lower than the rate observed in the final year of the prepandemic period (2019). The STA rate was lower in HK than in other countries or regions during the pandemic [ 12 , 27 , 28 ]. Several factors may have accounted for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 136 patients participated in Phatthranit Phattharapornjaroen et al, a single-center, retrospective cohort study in Thailand to evaluate the characteristics and prognosis of patients who experienced out-of-hospital cardiac arrest during and before the COVID-19 pandemic ( 15 ). Hypertension and diabetes were present in 46.67% and 25% of people, respectively ( 15 ).…”
Section: Discussionmentioning
confidence: 99%